Effect of Coolant Temperature and Stirring Rate in the Separation of Oil from Bilge Water using a Stirred Freeze Crystallizer - Mustapha, S.N.A. (Institute of Physics Publishing, 2020)
Each year, marine activities has contributed to nearly half of the discharged oil into the oceans, where 10 of it were dumped bilge oil. The tankers release oily and chemical residue, causing pollution to the marine environment due to excessive contamination of bilge water. Therefore, all marine ships over 400 tons are required to install an oil-water separator (OWS) system on board to limit the discharge of oil into the oceans. However, the current OWS technologies such as gravity and centrifugation method have difficulties to comply with the oil/grease discharge standard of 15 mg/L set by Malaysia's Department of Environment (DOE). This paper aims to introduce progressive freezing (PF) process as a new OWS method where it separates two liquid compounds based on their freezing point difference. One with higher freezing point will solidify first while another one will remain as liquid. In this study, the effect of coolant temperature and stirring rate towards oil/grease values were investigated. It was found that the highest efficiency of the PF process was obtained at stirring rate of 200 rpm and coolant temperature of -6Â°C. In addition, the best oil/grease value obtained was found to be lower than the discharge standard permitted by the Department of Environment (DOE), Malaysia. Â© 2020 IOP Publishing Ltd.